ADSORPTION OF SOME TOXIC METAL IONS ONTO WEST AFRICAN BOXWOOD (Naucleadiderrichii, MERRILL) SEED EPICARP DOPED WITH NANOPARTICLES (2014)
The quest to protect the environment from toxic metal ions pollution has led to the development of simple, cheap, adaptable and environmentally friendly techniques for the removal of these pollutants from wastewaters. Biosorbents which are biodegradable and locally available have been used for the removal of toxic metal ions from wastewaters. However, there are no reports on the use of Naucleadiderrichii Seed Epicarp(NDSE) and its nanoparticles-doped derivatives. Hence, this study was aimed at investigating the adsorption capacities of NDSE and its nanoparticles-doped derivatives for some toxic metal ions from simulated wastewaters. Identified NDSE were collected from Forest Research Institute of Nigeria, Ibadan. They were oven dried at 602 C, pulverised, sieved to 450 m and stored in airtight plastics at room temperature. The MnO2, mesoporous SiO2, graphene oxide and TiO2 nanoparticles were prepared by hydrothermal, liquid templating, chemical oxidation and sol-gel methods respectively. Thereafter, NDSE was doped with the nanoparticles to give NDSE-MnO2 (NMD), NDSE-Mesoporous SiO2 (NMS), NDSE-Graphene Oxide/Mesoporous SiO2 (NGM) and NDSE-TiO2 (NTD). The nanoparticles, native and nanoparticles-doped adsorbents were characterised by various techniques including scanning electron microscopy, transmission electron microscopy and surface area/porosity analysis. Adsorption studies were carried out using 20-500 mg of adsorbents to remove 20-100 mg/L toxic metals solution containing Cr(III), Cd(II) and Pb(II) ions for 0.5-180 min (agitation time), 125 rpm (agitation speed) at 303-333 K. The supernatants from the mixtures were analysed for toxic metal ions adsorbed using inductively coupled plasma-optical emission spectrometer. The native and nanoparticles-doped adsorbents had varying surface morphologies. The nanoparticles were 10-100 nm with large surface areas, while the nanoparticles-doped adsorbents were 10-200 m with greater surface areas than that of the native adsorbent. The removal of Cr(III), Cd(II) and Pb(II) ions per unit weight by the native and nanoparticles-doped adsorbents decreased with increase in adsorbent dose from 20 to 500 mg and were in the order NGM>NMS>NTD>NDSE>NMD. Adsorption of Cr(III), Cd(II) and Pb(II) ions on the five adsorbents increased with time from 0.5-180 min, initial metal ion concentration from 20 to 100 mg/L and temperature from 303 to 333 K. The ?H, ?G and ?S values for the removal of Cr(III), Cd(II) and Pb(II) ions by NDSE indicated reactions that were endothermic and spontaneous with decrease in entropy. Those of Cr(III), Cd(II) and Pb(II) ions on NMS and NGM were endothermic and spontaneous with increase in entropy. Those of NMD and NTD were endothermic and non spontaneous with decrease in entropy. The highest and lowest adsorptions respectively were 8.00.02 mg/g of Pb(II) ion on NGM and 3.10.02 mg/g of Cr(III) ion on NMD at 20 mg/L. Naucleadiderrichii seed epicarp doped with graphene oxide/mesoporous SiO2 nanoparticles adsorbed toxic metal ions more than the other adsorbents. The Naucleadiderrichii seed epicarp doped with MnO2 nanoparticles adsorbed lesser than the native adsorbent.